Physical modeling of glacier contact with bedrock (experiment) - V. P. Epifanov; A. F. Glazovsky; N. I. Osokin (Лëд и снег, 2015)
Studies of the adhesive strength of glacial ice connection with bedrock has been studied using the analysis of the amplitude-frequency characteristics of acoustic emission (AE) in the frequency range from 15 Hz to 20,000 Hz. Identification of signal source on bed is based on physical modeling of adhesive ice fracture at the complex shear and patterns of elastic waves propagation in the ice using data on ice thickness of the ice and its acoustic properties. The experimental dependence of the ice and serpentinite substrate adhesive strength with temperature (from 0 °C to −30 °C) has been obtained at constraint axial shear. It is shown that the destruction of adhesive ice contact with substrate begins long before the maximum shear stress achieved, and AE signals in the coordinates amplitude-frequency-time have been obtained for the for static friction and sliding parts of deformation curves. Influence of shear to normal stresses ratio on the adhesive ice/substrate strength has been shown. Influence of the ratio of longitudinal and transverse shear stresses on the adhesive bond strength of ice to the substrate has been shown. The natural glacier spectra revealed periodic reduction of AE signals frequency in the middle range of frequencies. The similar effect of AE signals shifting along the frequency axis to the low frequency domain was obtained by testing of freshwater ice samples and related with expansion of the destruction scale. Practical application of the strain AE results for remote determination of the local glacial stability and for studies of glacier ice mechanics is discussed.